Logic model framework for considering the inputs, processes and outcomes of a healthcare organisation–research partnership. Issue 9 (11th December 2019) - Tabriz, Amir Alishahi; Flocke, Susan A; Shires, Deirdre; Dyer, Karen E; Schreiber, Michelle; Elston Lafata, Jennifer
Abstract : Background: The published literature provides few insights regarding how to develop or consider the effects of knowledge co-production partnerships in the context of delivery system science. Objective: To describe how a healthcare organisation–university-based research partnership was developed and used to design, develop and implement a practice-integrated decision support tool for patients with a physician recommendation for colorectal cancer screening. Design: Instrumental case study. Participants: Data were ascertained from project documentation records and semistructured questionnaires sent to 16 healthcare organisation leaders and staff, research investigators and research staff members. Results: Using a logic model framework, we organised the key inputs, processes and outcomes of a healthcare organisation–university-based research partnership. In addition to pragmatic researchers, partnership inputs included a healthcare organisation with a supportive practice environment and an executive-level project sponsor, a mid-level manager to serve as the organisational champion and continual access to organisational employees with relevant technical, policy and system/process knowledge. During programme design and implementation, partnership processes included using project team meetings, standing organisational meetings and one-on-one consultancies to provide platforms for shared learning and problem solving. Decision-making responsibility was shared between the healthcare organisation and research team. We discuss the short-term outcomes of the partnership, including how the partnership affected the current research team's knowledge and health system initiatives. Conclusion: Using a logic model framework, we have described how a healthcare organisation–university-based research team partnership was developed. Others interested in developing, implementing and evaluating knowledge co-production partnerships in the context of delivery system science projects can use the experiences to consider ways to develop, implement and evaluate similar co-production partnerships.